2017
DOI: 10.1002/mp.12699
|View full text |Cite
|
Sign up to set email alerts
|

Relative dosimetry with an MR‐linac: Response of ion chambers, diamond, and diode detectors for off‐axis, depth dose, and output factor measurements

Abstract: The magnetic field of the MR-linac alters the effective point of measurement of ionization chambers, shifting it both downstream and laterally. Shielded diodes produce incorrect and misleading dose profiles. The output factor measured at the point of peak intensity in the lateral dose distribution is more robust than the conventional output factor (measured at central axis). Diodes are not recommended for output factor measurements in the magnetic field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 29 publications
0
72
0
2
Order By: Relevance
“…The dose deposited at tissue‐air interfaces can increase due to the electron returning effect (ERE), which can also be affected by the surface orientation where the photon beam enters or exits . The dosimetric response of QA devices (especially the detectors used for beam calibration) in magnetic fields have also been studied, focusing mainly on the absolute dose response of the detectors. The effect of the magnetic field on the detectors is demonstrated not only through the trajectory path deflection of the secondary electrons in the medium surrounding and inside the volume of the gas‐filled or solid detector, but also through the change of the intrinsic properties of detectors such as charge carrier versus lattice defect recombination, polarity effect, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose deposited at tissue‐air interfaces can increase due to the electron returning effect (ERE), which can also be affected by the surface orientation where the photon beam enters or exits . The dosimetric response of QA devices (especially the detectors used for beam calibration) in magnetic fields have also been studied, focusing mainly on the absolute dose response of the detectors. The effect of the magnetic field on the detectors is demonstrated not only through the trajectory path deflection of the secondary electrons in the medium surrounding and inside the volume of the gas‐filled or solid detector, but also through the change of the intrinsic properties of detectors such as charge carrier versus lattice defect recombination, polarity effect, etc.…”
Section: Introductionmentioning
confidence: 99%
“…For the ionization chamber, however, when the field size is sufficiently larger than the detector's diameter, an additional magnetic field and beam quality correction factor can be applied to the original calibration coefficient, obtained without the magnetic field, to obtain the correct absolute dose calibration in the presence of the magnetic field. The effective point of measurement (EPOM) of the ionization chamber is shifted not only in the beam direction but also laterally, perpendicular to both the beam and the magnetic field direction. According to O'Brien et al, the measured lateral shift in the dose distribution was independent of depth and field size from 2 × 2 cm 2 to 10 × 10 cm 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Some groups have investigated the response of point diodes, diode arrays, and diamond detectors in fields of both orientations and varying strengths. More recently, there have been studies on the effects on relative dosimetry . O’Brien et al examined changes in the relative response for shielded and unshielded diodes, diamond, and three different sized ionization chambers.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there have been studies on the effects on relative dosimetry. 20,[27][28][29] O'Brien et al 2 examined changes in the relative response for shielded and unshielded diodes, diamond, and three different sized ionization chambers. They concluded that the diodes and diamond were underestimating the lateral shift in profiles characteristic of perpendicular MRI-linacs.…”
Section: Introductionmentioning
confidence: 99%
“…A dosimetria nesses aparelhos é muito importante, pois em qualquer tratamento é necessário que a dose planejada seja igual à dose que será entregue ao paciente (ABAZA, 2016). Os dosímetros que são normalmente utilizados em radioterapia são os dosímetros termoluminescentes (TLDs), câmaras de ionização e filmes radiocrômicos (ALQATHAMI et al, 2016;PAUKSTYTE, S.;URBONAVICIUS, 2017;SCALCHI et al, 2017;ALDELAIJA et al, 2018;HAURI, SCHNEIDER, 2018;O'BRIEN et al, 2018;SINGH et al, 2018). Com o uso dos dois primeiros dosímetros é possível obter informações dosimétricas ponto a ponto, enquanto com o uso dos filmes radiocrômicos é possível obter uma informação bidimensional de dose.…”
Section: Capítulo 1: Introduçãounclassified